Answer:
x = ![\frac{9}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B9%7D%7B4%7D)
Step-by-step explanation:
Given
-
=
← factor denominator
-
= ![\frac{4}{x(x+1)}](https://tex.z-dn.net/?f=%5Cfrac%7B4%7D%7Bx%28x%2B1%29%7D)
[ x ≠ 0, x ≠ - 1 as these would make the terms undefined ]
Multiply through by x(x + 1)
4x² - 5(x + 1) = 4
4x² - 5x - 4 = 4 ( subtract 4 from both sides )
4x² - 5x - 9 = 0 ← in standard form
(x + 1)(4x - 9) = 0 ← in factored form
Equate each factor to zero and solve for x
x + 1 = 0 ⇒ x = - 1
4x - 9 = 0 ⇒ 4x = 9 ⇒ x = ![\frac{9}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B9%7D%7B4%7D)
However, x ≠ - 1 for reason given above, then
solution is x = ![\frac{9}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B9%7D%7B4%7D)